IMPLEMENTASI METODE IMLA’ DALAM MENINGKATKAN KETERAMPILAN MENULIS ARAB SISWA PONDOK PESANTREN TAHFIZHUL QUR’AN AN-NAHL GRABAG MAGELANG - Syahidah Ula; Zahrodin Fanani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the implementation of the imla’ method in improving the Arabic writing skills of students at Pondok Pesantren Tahfizhul Qur’an An-Nahl Grabag Magelang. The background of this study is the limited ability of students to write Arabic accurately. The study aims to describe the implementation process of the imla’ method and to analyze its effectiveness in enhancing students’ Arabic writing skills. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The findings indicate that the implementation of the imla’ method, which consists of listening, writing, and evaluation stages, has a positive impact on improving students’ ability to write Arabic accurately. However, several challenges were identified during its implementation, including limited instructional time and differences in students’ educational backgrounds. The implications of this study suggest that the imla’ method can serve as an effective alternative for improving Arabic writing skills when implemented in accordance with students’ learning needs.